The effect of avocado butter to stability of avocado emollient cream - Teti Indrawati; Yuanita Sari (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
The characteristic of emollient cream that contained of avocado butter as anti-aging is influenced by amount of avocado butter used. The research has a purpose to exploit and develop usage of avocado butter in the field of cosmetic. The research has done by making A/M cream used 1-11% avocado butter with melting and mixing method at temperature of 70-75 °C. Stability of product creams were be evaluated, and tested with accelerated test using elevated temperature. The result showed that concentration of avocado butter between 1-11% can be made become W/O emollient cream. The cream stability was progressively influenced by amount of avocadobutter, the increasing of avocado butter would make progressively good stability, the stability go down at 7% concentration. The best stability creams has shown by cream that contain 5% avocado butter,Key words: avocado butter, A/M cream type, emollient cream, stability of cream